Treatment And Incidence Of Von Willebrand's Disease In The Republic Of Uzbekistan (Texas Journal of Medical Science, 2022)
Von Willebrand disease (VW) is the most common coagulopathy caused by quantitative and qualitative von Willebrand factor (vWF) deficiency. BV affects about 1% of the population. However, most patients with VWD usually have no symptoms. The number of patients with BV who need ongoing treatment is comparable to that of hemophilia. Approximately 70% of patients with VWD have a mild disease, while the remaining 30% of patients have a moderate or severe disease [1]. The most characteristic and specific symptom in von Willebrand disease is bleeding from the mucous membranes of the mouth, nose, and internal organs. Symptoms of bleeding vary from moderately severe to extremely severe, proceeding mainly according to the microcirculatory type. Patients with severe factor VIII deficiency experience profuse and prolonged bleeding (nasal, gingival, uterine), as well as hemorrhages in muscles and joints. In addition, prolonged bleeding may occur with injuries, tooth extractions, and operations. In childhood, there are often bleeding from the mucous membranes of the oral cavity, nosebleeds, bruises on the skin. A more severe course of hemorrhagic diathesis is observed during or shortly after infectious diseases. The most likely trigger for bleeding in the presence of an infection is a violation of vascular permeability. The most likely trigger for bleeding in the presence of an infection is a violation of vascular permeability. As a result, spontaneous bleeding of the diapedetic type appears.